ChemInform Abstract: M2Cd3B16O28 (M: Rb, Cs): Two Isostructural Alkali Cadmium Borates with a New Type of Borate Layer. Issue 39 (5th September 2013) - Dong, Xiaoyu; Shi, Yunjing; Zhou, Zhongxiang; Pan, Shilie; Yang, Zhihua; Zhang, Bingbing; Yang, Yun; Chen, Zhaohui; Huang, Zhenjun
Abstract Single crystals of the title compounds are prepared from mixtures of M2CO3 (M: Rb, Cs), CdO, and H3BO3 at ratios of 1:1:10 (Pt crucible, 300, 600, and 850 °C, 12 h each).